2000
DOI: 10.1115/1.1287591
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Optimization of Machining Parameters for Dimensional Instability Control in Aero Gas Turbine Components Made of Inconel 718 Alloy

Abstract: Aero gas turbine components made of Inconel 718 superalloy revealed significant dimensional instability after machining. The dimensional instability is a manifestation of alterations in residual stresses and microstructure, which are influenced by machining parameters. This paper presents a simultaneous optimization technique used to control the dimensional instability in turning operation. Empirical equations are established for predicting surface residual stresses, surface finish, dimensional instability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Moreover, because of residual stress distribution generated by machining operations combined with those stresses generated by previous manufacturing process, dimensional instability (distortion) can occur after machining. Subhas et al (2000aSubhas et al ( , 2000b found the Inconel 718 more prone to dimensional instability than the titanium alloys, although the latter has a lower modulus of elasticity. According to them, this phenomenon was not noticed in other nickel-based alloys and may be due to the presence of γ ″ phase.…”
Section: Nickel-based Alloysmentioning
confidence: 99%
“…Moreover, because of residual stress distribution generated by machining operations combined with those stresses generated by previous manufacturing process, dimensional instability (distortion) can occur after machining. Subhas et al (2000aSubhas et al ( , 2000b found the Inconel 718 more prone to dimensional instability than the titanium alloys, although the latter has a lower modulus of elasticity. According to them, this phenomenon was not noticed in other nickel-based alloys and may be due to the presence of γ ″ phase.…”
Section: Nickel-based Alloysmentioning
confidence: 99%
“…This phenomenon brings problems in structural assembly, as it destroys the structural integrity. Inconel 718 has revealed the dimensional instability after machining, and it is more prone to dimensional changes in comparison with both titanium alloys and mild steels [79,80].…”
Section: Residual Stressesmentioning
confidence: 99%
“…This phenomenon brings problems in structural assembly, as it destroys the structural integrity. Inconel 718 has revealed dimensional instability after machining, and it is more prone to dimensional changes in comparison with either titanium alloy or mild steel [67,68].…”
Section: Residual Stressesmentioning
confidence: 99%